1996
DOI: 10.1038/381603a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of transcription factors a Brn-3.1 and Brn-3.2 in auditory and visual system development

Abstract: The neurally expressed genes Brn-3.1 and Brn-3.2 (refs 1-6) are mammalian orthologues of the Caenorhabditis elegans unc-86 gene that constitute, with Brn-3.0 (refs 1-3,8,9), the class IV POU-domain transcription factors. Brn-3.1 and Brn-3.2 provide a means of exploring the potentially distinct biological functions of expanded gene families in neural development. The highly related members of the Brn-3 family have similar DNA-binding preferences and overlapping expression patterns in the sensory nervous system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
344
3
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(362 citation statements)
references
References 27 publications
13
344
3
2
Order By: Relevance
“…Thus, the closely related POU family transcription factors Brn-3a, Brn-3b and Brn-3c were originally identified on the basis of their distinct but overlapping patterns of gene expression in the developing and adult nervous systems [3][4][5][6] and inactivation of the individual genes encoding these factors has been shown to produce defects in the development of specific parts of the nervous system. [7][8][9] However, expression of Brn-3a and Brn-3b has also been observed in nonneuronal cells notably, in the testis, 10 breast 11 and cervix. 4,12 This expression of Brn-3a in neuronal and some nonneuronal cell types is paralleled by their overexpression in tumors of neuronal and nonneuronal origin.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the closely related POU family transcription factors Brn-3a, Brn-3b and Brn-3c were originally identified on the basis of their distinct but overlapping patterns of gene expression in the developing and adult nervous systems [3][4][5][6] and inactivation of the individual genes encoding these factors has been shown to produce defects in the development of specific parts of the nervous system. [7][8][9] However, expression of Brn-3a and Brn-3b has also been observed in nonneuronal cells notably, in the testis, 10 breast 11 and cervix. 4,12 This expression of Brn-3a in neuronal and some nonneuronal cell types is paralleled by their overexpression in tumors of neuronal and nonneuronal origin.…”
Section: Introductionmentioning
confidence: 99%
“…IHCs of Pou4f3-α10 mice express α10 mRNA after the onset of hearing It has been reported that the Pou4f3 transcription factor is expressed in hair cells from early embryonic until adult stages (Erkman et al 1996) and that Cre expression driven by the Pou4f3 promoter starts as early as embryonic day 13.5 in a transgenic mouse (Sage et al 2006). Thus, the use of the Pou4f3 promoter has become a useful tool for transgenic expression of genes in cochlear hair cells.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Chrna9 continues to be transcribed into adult stages (Elgoyhen et al 1994). To further analyze this critical developmental change near the onset of hearing, we generated a transgenic mice whose IHCs constitutively express α10 into adulthood by expressing the α10 cDNA under the control of the mouse Pou4f3 gene promoter, a hair cell transcription factor (Erkman et al 1996). We reasoned that if the lack of responses to ACh after the onset of hearing was due to the cessation in transcription of Chrna10, constitutive expression of the α10 subunit would result in functional receptors.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest-expressed genes specifically in HCs is murine atonal homolog-1 (Math-1), a basic helix-loop-helix transcription factor, which first appears in the sensory epithelium of the utricle, saccule, semicircular canals, and cochlea, and becomes restricted to HCs by the end of gestation (Bermingham et al, 1999;Kawamoto et al, 2003). Another early "HC-specific" gene product is Brn3.1 (POU4F3, Brn3c), a POU family transcription factor essential for HC differentiation and survival (Erkman et al, 1996;Ryan, 1997;Xiang et al, 1997). Mutations in Brn3.1 (DFNA15) were shown to cause familial adult onset progressive hearing loss in humans (Vahava et al, 1998).…”
Section: Markers Of Hc and Scmentioning
confidence: 99%